2020
DOI: 10.15421/2020_164
|View full text |Cite
|
Sign up to set email alerts
|

Effect of iron, zinc and boron on the growth, physiological state, productivity and storability of Allium Sativum L.

Abstract: The importance of studying in agriculture the impact of individual micronutrients on the course of production processes and their impact on the quality of garlic is an important issue. The influence of iron, zinc and boron in different norms against the background of the recommended norm NPK. The research results showed significant increasing of chlorophyll content by the application of Iron 10 and 20 kg/ha – 12.0 and 16.4%; by the application zinc increasing of chlorophyll was significant on all variants – 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…In case of treatment with different boron levels, highest ascorbic acid content (3.48 mg/100 g) was found with treatment B 3 (boron spray at 200 ppm), which was closely followed (3.34 mg/100 g) bytreatment B 2 (boron spray at 150 ppm). Similar results showing an increase in ascorbic acid content with an increase in rate of boron application to the soil were obtained by Yatsenko et al [20] while working with garlic. Treatment of roots with spray at different times also had a significant impact on ascorbic acid content in roots.…”
Section: Resultssupporting
confidence: 86%
“…In case of treatment with different boron levels, highest ascorbic acid content (3.48 mg/100 g) was found with treatment B 3 (boron spray at 200 ppm), which was closely followed (3.34 mg/100 g) bytreatment B 2 (boron spray at 150 ppm). Similar results showing an increase in ascorbic acid content with an increase in rate of boron application to the soil were obtained by Yatsenko et al [20] while working with garlic. Treatment of roots with spray at different times also had a significant impact on ascorbic acid content in roots.…”
Section: Resultssupporting
confidence: 86%
“…b ratio pointed out a stronger positive relationship between Zn and chlorophyll a synthesis. Zn was reported as an element that increases the antioxidant enzyme activity in onion [41], and this research provides an explanation for the negative correlation noted for Zn content and antioxidant activity of onion bulbs in the present study. The genetic variability may be one of the possible reasons for differences between the onion cultivars' Zn content in bulbs.…”
Section: Discussionsupporting
confidence: 75%
“…The lowest values of all the yield attributes were associated with the NPK control (Table 3). The increased yield might be attributed to higher availability of zinc and its influence on enhanced enzymatic and photosynthetic activity with greater zinc translocation rate (Yadav et al 2018;Zakiullah et al, 2019;Yatsenko et al, 2020). Bulb size and diameter are the most important factors closely related with yield per hectare, which also increased with the addition of zinc sulphate.…”
Section: Growth and Yield Attributesmentioning
confidence: 99%
“…Hence balanced fertilizer schedule must also include zinc addition and optimized based on crop requirement and soil fertility status (Yadav et al, 2018). Studies have demonstrated that, supply of zinc increased the transport and accumulation of zinc in plants and its use efficiency by plants (Yousuf et al, 2016;Yatsenko et al, 2020). Some studies have shown that zinc fertilization increased the crop growth and yield in cereals, oilseeds and vegetables (Cakmak et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation